2022
DOI: 10.1080/21645515.2022.2043719
|View full text |Cite
|
Sign up to set email alerts
|

Public acceptability of COVID-19 vaccines and its predictors in Middle ‎Eastern/North African (MENA) countries: a systematic review‎

Abstract: Introduction COVID-19 vaccines emerged as a worldwide hope to contain the pandemic. However, many people ‎are still hesitant to receive these vaccines. We aimed to systematically review the public knowledge, perception, and acceptability of COVID-19 vaccines in the Middle East and North Africa (MENA) countries and the predictors of vaccine acceptability in this region. Methods We systematically searched databases of PubMed, Scopus, Web of Science, and Cochrane and retri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(55 citation statements)
references
References 63 publications
3
52
0
Order By: Relevance
“…Fourth, concerns about the safety and efficacy of the vaccine are particularly pronounced in COVID-19 vaccination practices, partly, as we found earlier [28] , [12] , due to the expedited vaccine development process [23] , [1] , [6] ; Latkin et al, 2021; [26] , [3] and the amplification of existing concerns during the pandemic (Rhuginis et al 2022).…”
Section: Background and Contextmentioning
confidence: 70%
See 2 more Smart Citations
“…Fourth, concerns about the safety and efficacy of the vaccine are particularly pronounced in COVID-19 vaccination practices, partly, as we found earlier [28] , [12] , due to the expedited vaccine development process [23] , [1] , [6] ; Latkin et al, 2021; [26] , [3] and the amplification of existing concerns during the pandemic (Rhuginis et al 2022).…”
Section: Background and Contextmentioning
confidence: 70%
“…Existing research has identified a set of themes that inform COVID-19 vaccination practices across countries. First, pre-existing attitudes regarding vaccinations shape stances towards a COVID-19 vaccine, both in favour of getting vaccinated [6] and for those who report hesitation [1] , [21] .…”
Section: Background and Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid the detrimental repercussions of this unfounded vaccine hesitancy, health care workers should aim to dispel the misconceptions by providing accurate information for people about the potential benefits of being COVID‐19 vaccinated. Also, ensuring validity of vaccine‐related information through social networks is of great importance in eliminating conspiracy beliefs about vaccination 62 . Moreover, to safely vaccinate susceptible individuals, they should be aware of the possible COVID‐19 vaccine hypersensitivity reactions and explicit protocols for managing them.…”
Section: Bodymentioning
confidence: 99%
“…Although allergic patients should not generally be excluded from the vaccination program, this may lead to a deep distrust of vaccines and delay deploying counter-pandemic measures fast enough to balance out devastating economic, social, and public health consequences of the pandemic.To avoid the detrimental repercussions of this unfounded vaccine hesitancy, health care workers should aim to dispel the misconceptions by providing accurate information for people about the potential benefits of being COVID-19 vaccinated. Also, ensuring validity of vaccine-related information through social networks is of great importance in eliminating conspiracy beliefs about vaccination 62. Moreover, to safely vaccinate susceptible individuals, they should be aware of the possible COVID-19 vaccine hypersensitivity reactions and explicit protocols for managing them.4 | CONCLUSIONIn summary, COVID-19 vaccines introduce several advantages that outweigh their potential risks, such as allergic reactions that occur through different pathways and whose proper management can arrest severe outcomes.…”
mentioning
confidence: 99%